Elaboração de licor de piquiá e pesquisa de mercado para licores de frutas em Santarém - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This work was prepared in the format of two scientific articles. The objective of the first article was elaborate, evaluate the acceptability and physicochemically characterize a piquia liqueur, obtaining a product without the characteristic bitterness of the fruit. The pyrenes and cachaça were stored in maceration to obtain the alcoholic extract. The extract was filtered, syrup added and bottled. Three syrup:extract ratios were tested, being T1-2:1, T2-1:1 and T3-1:2. Sensory analysis was performed with 37 tasters using an acceptance test with a scale of 9 to 1 for the attributes color, flavor, aroma, appearance, sweetness and overall impression; and scale from 5 to 1 for purchase intent; and alcoholic taste. pH, °Brix and alcohol content were also evaluated. Data were submitted to analysis of variance and, when significant, to the Tukey test. In the sensory evaluation, there was no difference between treatments, with scores between 6 (I liked it slightly) and 7 (I liked it regularly), with no rejection of the samples. T2 and T3 had good purchase intention, grade 4 (probably would buy). The acceptability index was higher than 70% for the three formulations, except sweetness (62.44%) for T1. T2 and T3 obtained the highest percentages of acceptability index, as well as market intention. The °Brix differentiated between T1, T2 and T3, respectively, 43.07, 36.22 and 28.83. The results suggest T2 and T3 as the best formulations for the elaboration of piquia liqueur. The acceptability index was higher than 70% for the three formulations, except sweetness (62.44%) for T1. T2 and T3 obtained the highest percentages of acceptability index, as well as market intention. The °Brix differed significantly, respectively, 43.07, 36.22 and 28.83. The results suggest T2 and T3 as the best formulations for the elaboration of piquia liqueur. The objective of the second article was to carry out market analysis for fruit liqueurs in the city of Santarém-PA, through the consumer profile, consumption, purchase behavior of fruit liqueurs and estimate of production cost of a piquia liqueur. For this purpose, an online questionnaire was prepared and the data analyzed using descriptive statistics. It was observed in the consumer profile that most respondents were female (52%), predominantly aged between 18 and 28 years (44%). It was found that the highest frequency of consumption is once a year (28%) and once a month (28%). Regarding purchasing behavior, it was found that 48% buy liqueur once a year, highlighting difficulties in finding the product, establishments and the desired flavor. As for the sale value, it was estimated at R$23.72 for 500mL of piquiá liqueur. Consumers of fruit liqueurs in Santarém-PA have a low frequency of purchase and consumption of the product, suggesting a relationship with reported difficulties in finding the product or flavor options. The sale value can be reduced with additional survey of suppliers that offer cheaper raw material.
Keywords: Amazônia; Alimento; Análise sensorial; Tecnologia de bebidas; CNPQ:: CIÊNCIAS BIOLÓGICAS